A coherent life. Issue 11 (November 2018) - Carney, P.; Eberly, Joseph
Emil Wolf died in June 2018 at the age of 95. The father of optical coherence theory was at the University of Rochester for nearly 60 years. A memorial in August at the university attracted more than 150 attendees from around the world.